Synthesis and characterization of polyaniline in CTAB/hexanol/water reversed micelle - Xing, Shuangxi; Chu, Ying; Sui, Xiaomeng; Wu, Zisheng (Journal of materials science, 2005)
In this report, we selected cetyltrimethyl ammonium bromide (CTAB) as a surfactant to form reversed micelles in or der to make a further study of the synthesis of PANI. More comprehensive characteristics were performed to provide valuable information of the template synthe sis of PANI, and from the results we could find that CTAB was not a dopant in the above research. As far as we know, it was the first time CTAB was used as a surfactant to form reversed micelles for synthesis of PANI. In our experiment, aniline was purified by distillation in vacuum prior to use. Ammonium peroxy disulfate (APS), CTAB, hexanol, methanol, ether, and hydrochloric acid were used as received. Deinonized water was used in all the experiments.